ChemInform Abstract: Synthesis of New Diketopiperazines, Thiolation to Thiodiketopiperazines, and Examination of Their ROS‐Generating Properties. Issue 11 (February 2016) - Zhong, Sabilla; Wandler, Angela E. E.; Schepers, Ute; Nieger, Martin; Braese, Stefan
Abstract: A broad spectrum of symmetrical and unsymmetrical diketopiperazines is prepared from 9 optically pure amino acids.